PREDIKSI NILAI TUKAR RUPIAH MENGGUNAKAN METODE MAMDANI - Indra Suyahya; Wulan Anggraeni (Universitas Indraprasta PGRI, 2016)
The main purpose of this study was to find out whether the mamdani methode can predict foreign exchange rate based on inflation rate. The result of descriptive calculation using SPSS 22 show that the mean, median, mode, standard deviation, minimum and maximum based on the inflation rate in order are 6.0548; 6.0650; 4.53; 1.63194; 3.56; and 8.79. While the mean, median, mode, standard deviation, minimum and maximum respectively for fpreign exchange is, 11164.48; 11431.5; 9687; 1554.65; 9026; 14369. The result of MAPE value was 9,35%. It’s mean mamdani method can be used as reference for predicting foreign exchange rate. Keywords: Prediction, Exchange Rate and Mamdani